The Origins of Indonesian Democracy and Its Implications in Indonesian Politics - Nurdin, Iing; Sardini, Nur Hidayat; Oktaviani, Jusmalia (Archives of Business Research, 2023)
The practice of democracy and political life cannot be separated from the roots or origins that was formed the basis, including in Indonesia. This article aims to examine and seek explanations regarding the roots of democracy in Indonesia. This analysis begins with a historical perspective. There are many questions about Indonesian history that need to be answered in order to understand the problems and practices of democracy in Indonesia. Has Indonesia historically had experience in practicing democracy before its independence? What are the historical reasons for the absence of democracy in contemporary Indonesia? Are there democratic values in Indonesian history that can be used as a basis for upholding contemporary democracy? The results of the analysis show that there is still debate among Indonesian experts, some state that Indonesia has no roots in democracy, while other experts state the opposite that the roots and practices of democracy in Indonesia have existed for a long time and are practiced in people’s daily lives. Indonesia.